2023
DOI: 10.1097/dss.0000000000003630
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lentigines: A Systematic Review

Abstract: BACKGROUND Treatments for solar lentigines include topical and physical therapies, including chemical peels, lasers, intense pulsed light, and cryotherapy. A direct comparison of treatment methods and their efficacy is lacking. OBJECTIVE To compare treatment efficacy and adverse events for different treatment modalities for lentigines. METHODS Cochrane, MEDLINE, and Embase databases were searched on August 25, 2021. Studies were included if they met our predetermined population, intervention, comparator, outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This concept is supported by several high‐quality studies which have also found that combination therapies have superior efficacy rates as compared to monotherapy in hyperpigmentation disorders. For example, a systematic review by Mukovozov et al 53 . evaluating treatment modalities for lentigines and their corresponding clinical outcomes found that combination therapies had greater efficacy rates as compared to laser, topical, cryotherapy and peel monotherapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is supported by several high‐quality studies which have also found that combination therapies have superior efficacy rates as compared to monotherapy in hyperpigmentation disorders. For example, a systematic review by Mukovozov et al 53 . evaluating treatment modalities for lentigines and their corresponding clinical outcomes found that combination therapies had greater efficacy rates as compared to laser, topical, cryotherapy and peel monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…52 This concept is supported by several high-quality studies which have also found that combination therapies have superior efficacy rates as compared to monotherapy in hyperpigmentation disorders. For example, a systematic review by Mukovozov et al 53 evaluating treatment modalities for lentigines and their corresponding clinical outcomes found that combination therapies had greater efficacy rates as compared to laser, topical, cryotherapy and peel monotherapies. Similarly, a systematic review and meta-analysis of randomized control trials evaluating the efficacy of available interventions for melasma found that 87% (n = 27/31) of included studies demonstrated a superior efficacy of combination therapies compared to monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…AHAs have also been shown to modulate the expression of genes implicated in skin pigmentation, leading to an overall reduction in melanin synthesis and an improvement in hyperpigmentation [26]. In a systematic review investigating treatments for lentigines, a common form of hyperpigmentation, 58% of individuals experienced a complete or partial response following chemical peels with AHA/BHAs [27]. These findings further underscore the multifaceted mechanisms by which AHAs exert their beneficial effects on the skin.…”
Section: Mechanisms Of Actionmentioning
confidence: 95%
“…[7][8][9][10] Lentigines can be effectively treated with chemical peels, which resurface the superficial portion of the epidermis to remove undesirable pigment, thereby addressing extrinsic signs of photoaging. [11][12][13][14][15][16] Specifically, trichloroacetic acid (TCA) ,35% peels have been used for decades for superficial chemical peeling because of its efficacy, safety profile, and ability to correlate peel depth with color of surface frost. 17,18 The white frost caused by TCA peels is due to keratocoagulation or protein denaturation of membrane proteins.…”
mentioning
confidence: 99%